A micro-conductive polyimide coating diaphragm with energy release function and a preparation method thereof

CN120999252BActive Publication Date: 2026-11-03JIANGSU YUCHENG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511179624.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2026-11-03
Estimated Expiration
2045-08-22

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators suffer from insufficient temperature resistance, poor interface stability, and limited functionality in high-energy-density batteries. Traditional modified separator processes are complex and costly, making them difficult to scale up for application.

Method used

A three-dimensional conductive network was constructed by combining phosphorus-containing dianhydride monomers (DOPO derivatives) with modified carboxylated carbon nanotubes (MWCNTS-COOH) through in-situ polymerization and chemical bonding. A gradient pore size structure was designed, and a micro-conductive polyimide coated membrane was prepared by combining a one-step spraying and thermosetting process.

Benefits of technology

It achieves a synergistic effect of high safety, low impedance and mass production economy, improves the cycle life and electrolyte wettability of lithium-ion batteries, is compatible with high voltage and fast charging battery systems, and has passed UL94 V0 certification for high temperature stability and yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120999252B_ABST
    Figure CN120999252B_ABST
Patent Text Reader

Abstract

The application discloses a kind of micro-conductive polyimide coating diaphragm with energy release function, including porous substrate and composite coating coated on at least one side of porous substrate, and the composite coating includes the following components: polyimide matrix and modified carboxylated carbon nanotube, modified carboxylated carbon nanotube is uniformly dispersed in polyimide matrix;The porosity of composite coating is 40~60%, the average pore size is 0.1~0.5 μm, and the pore size is gradient distribution along the thickness direction, the surface layer pore size≤0.2 μm, the bottom layer pore size≥0.4 μm.The application further discloses a kind of preparation method of micro-conductive polyimide coating diaphragm with energy release function.In the application, flame retardant is realized by gas phase-coagulation phase synergistic mechanism, three-dimensional conductive network is constructed, performance conflict is avoided by in-situ polymerization chemical bonding, and dendrite block and ion transmission efficiency are considered by gradient pore size design.One-step spraying+heat curing process realizes submicron coating uniform adhesion, and process is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, and more particularly to a micro-conductive polyimide coated separator with energy slow-release function and its preparation method. Background Technology

[0002] As a core component of new energy vehicles, consumer electronics, and energy storage systems, the performance and safety of lithium-ion batteries are highly dependent on the technological level of the separator. The separator needs to possess multiple functions, including ion conduction, electronic insulation, mechanical support, and thermal stability. Currently, mainstream commercial separators are mainly made of polyolefin (PE / PP) materials, using dry or wet processes to prepare microporous structures, offering advantages such as low cost and mature technology. However, with the widespread adoption of high-energy-density batteries (such as NCM811 and silicon-carbon anodes), traditional separators have revealed significant defects: ① Insufficient temperature resistance: PE / PP has a melting point below 160℃, making it prone to melting and shrinkage at high temperatures, leading to internal short circuits (such as in needle penetration and overcharge scenarios); ② Poor interface stability: Insufficient electrolyte wettability (contact angle > 90°), exacerbating lithium dendrite growth and capacity decay; ③ Limited functionality: Only meeting basic isolation requirements, unable to adapt to advanced battery systems such as high-voltage (≥4.5V) and fast-charging (≥3C).

[0003] To address these issues, the industry has shifted towards developing composite modified diaphragms. For example, ceramic-coated diaphragms (Al2O3 / SiO2 coating) improve heat resistance through physical shielding, while aramid-coated diaphragms enhance safety by utilizing their intrinsic flame retardancy. Diaphragm modification research focuses on two main directions: material functionalization and structural design. ① Material functionalization: Introducing flame retardants (such as ammonium polyphosphate) or high-temperature resistant materials (such as PI) can improve safety, but the insulation properties of flame retardants significantly increase the diaphragm surface resistivity (>5Ω·cm). 2 This leads to increased battery polarization. While conductive materials (such as carbon nanotubes and graphene) can reduce impedance, their high conductivity and tendency to permeate when distributed alone in the coating can cause micro-short circuits even under normal battery use. ② Structural design: Optimizing ion transport paths through micro / nano structures such as gradient pore sizes and vertical channels, but traditional processes (such as phase separation methods) struggle to precisely control porosity and pore size distribution, resulting in poor mass production consistency. Complex processes (such as multi-layer coating and high-temperature sintering) and high costs restrict large-scale applications. For example, patent CN202410781427.3 introduces phosphorus-based or silicon-based flame retardants through complex processes, but most flame retardants are insulators, leading to a decrease in ionic conductivity (<1.5 mS / cm); patent ZL201811511920.4 requires multiple in-situ polymerization or nano-modification steps, with cumbersome processes (such as flame retardant grafting and multi-layer coating), increasing production costs by more than 30% and hindering large-scale production. Summary of the Invention

[0004] The purpose of this invention is to provide a micro-conductive polyimide coated diaphragm with energy slow-release function.

[0005] The present invention also provides a method for preparing a micro-conductive polyimide coated diaphragm with energy slow-release function.

[0006] The innovation of this invention lies in achieving synergistic performance through material innovation and process optimization. It employs a composite of a phosphorus-containing dianhydride monomer (DOPO derivative) and carboxylated carbon nanotubes (MWCNTS-COOH). DOPO achieves flame retardancy through a gas-phase-condensed-phase synergistic mechanism (LOI > 35%), while MWCNTS-COOH constructs a three-dimensional conductive network (sheet resistivity < 2 Ω·cm). 2 The two components are chemically bonded through in-situ polymerization, avoiding performance conflicts. Furthermore, a gradient pore size design (0.1μm for the surface layer and 0.5μm for the bottom layer) balances dendrite blocking and ion transport efficiency, with a porosity of 40-60% to adapt to highly wettable electrolytes, achieving structural optimization. A one-step spraying + thermosetting process achieves uniform submicron-level coating adhesion, simplifying the process and reducing mass production costs by 20%.

[0007] To achieve the above-mentioned objectives, the technical solution of this invention is as follows:

[0008] A micro-conductive polyimide coated membrane with energy-releasing function includes a porous substrate and a composite coating coated on at least one side of the porous substrate. The composite coating comprises the following components: a polyimide matrix and modified carboxylated carbon nanotubes. The modified carboxylated carbon nanotubes are uniformly dispersed in the polyimide matrix, and the content of the modified carboxylated carbon nanotubes is 0.5-1.5 wt% of the polyimide matrix. The modified carboxylated carbon nanotubes are formed by modifying the surface of carboxylated carbon nanotubes with a silane coupling agent. The polyimide matrix is ​​generated by in-situ polymerization of dianhydride monomers and diamine monomers. The dianhydride monomers contain DOPO derivative dianhydride monomers, and the DOPO derivative dianhydride monomers account for 3-8% of the total molar ratio of dianhydride monomers. The porosity of the composite coating is 40-60%, the average pore size is 0.1-0.5 μm, and the pore size is gradient distributed along the thickness direction, with the surface pore size ≤0.2 μm and the bottom pore size ≥0.4 μm.

[0009] Furthermore, the porous substrate is a polyolefin-based membrane, which is a polyethylene-based membrane or a polypropylene-based membrane, with a thickness of 3–20 μm and a porosity of 30–50%.

[0010] Furthermore, the DOPO derivative dianhydride monomer is DOPO-HQDA, and its chemical formula is [insert chemical formula here].

[0011] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane, and the amount of γ-aminopropyltriethoxysilane added is 5-10% of the mass of the carboxylated carbon nanotubes.

[0012] Furthermore, the dianhydride monomers, except for the DOPO derivative dianhydride monomers, are one or a mixture of two or more of biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), benzophenone tetracarboxylic dianhydride (BTDA), diphenyl ether tetracarboxylic dianhydride (ODPA), hexafluorodianhydride (6FDA), and bisphenol A type diether dianhydride (BPADA); the diamine monomers are one or a mixture of two or more of diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 4,4'-diaminodiphenylmethane (MDA), and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFDB); and the solvents are one or a mixture of two or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAc).

[0013] A method for preparing a micro-conductive polyimide coated separator with energy slow-release function includes the following steps:

[0014] A. Preparation of polyamic acid solution: Dissolve dianhydride monomer and diamine monomer in solvent, add carboxylated carbon nanotubes and silane coupling agent, disperse for 2-4 hours to form a spinning solution with a solid content of 10-25 wt%.

[0015] B. Fiber preparation: The spinning solution is electrospinned to prepare nanofiber materials with a diameter of 100-800 nm;

[0016] C. High-temperature imidization: Under nitrogen protection, the nanofiber material is heat-treated at 250-400℃ for 1-4 hours to complete the polyimide ring-closure reaction and obtain high-temperature imide material;

[0017] D. Slurry preparation: The high-temperature imide material, water-based binder, and pore-forming agent are uniformly dispersed in water to prepare a slurry with a solid content of 3-20%.

[0018] E. Coating and Pre-curing: The slurry is uniformly coated on the surface of the porous substrate and pre-cured at 50-60℃ for 5-10 minutes to obtain a pre-cured film;

[0019] F. Gradient drying: The pre-cured film is dried in two stages: the first stage is 60°C for 10 min, and the second stage is 120°C for 30 min to obtain a finished product with gradient pore size.

[0020] Furthermore, the aqueous adhesive is one or more of the following: aqueous PVDF emulsion, polyvinyl alcohol, polyethylene oxide, water-soluble acrylic adhesive, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyvinylpyrrolidone.

[0021] Furthermore, in step A, the carboxyl content of the carboxylated carbon nanotubes is 3-5 mmol / g, and in step D, the slurry viscosity is 500-800 mPa·s at 25°C.

[0022] Furthermore, the coating method in step E is one of spray coating, scraping coating, gravure coating, or dip coating.

[0023] Furthermore, the pore-forming agent in step D is a mixture of polyethylene glycol and acetone at a mass ratio of 1:3 to 5; the gradient pore size in step F has a surface pore size ≤0.2μm and a bottom pore size ≥0.4μm.

[0024] The beneficial effects of this invention are:

[0025] 1. This invention integrates high temperature resistance, flame retardancy, micro-conductivity, and gradient aperture, while also possessing high safety, low impedance, and economic efficiency for mass production. It features triple innovation in materials, structure, and process.

[0026] Functional Synergy: A pioneering in-situ polymerization bonding of DOPO flame retardant and MWCNTS-COOH conductive agent with polyimide matrix material solves the phase separation problem of traditional physical blending, achieving both flame retardancy (LOI ≥ 35%) and micro-conductivity (surface resistivity ≤ 2Ω·cm). 2 Dual-function synergy.

[0027] Structural innovation: Gradient pore size design (surface layer ≤0.2μm / bottom layer ≥0.4μm), balancing dendrite blocking and ion transport efficiency, with a porosity of 40-60% significantly improving electrolyte wettability (contact angle).

[0028] <20°).

[0029] Process economy: One-step molding of spraying and thermosetting, coating thickness <1μm, mass production efficiency increased by 50%, and cost reduced by 20% (compared to multi-layer coating / high temperature sintering process).

[0030] Performance Breakthrough: Improved Cycle Life: NCM811 batteries retain >80% capacity after 500 cycles (traditional flame-retardant separators <75%);

[0031] Enhanced safety: UL94 V0 certified, no shrinkage at high temperatures (200℃).

[0032] Mass production compatibility: Wide range of process parameters (e.g., MWCNTS-COOH content 0.5-1.5wt%), suitable for roll-to-roll production, with a yield rate >95%. Attached Figure Description

[0033] Figure 1 The surface pore structure of the product in Example 5.

[0034] Figure 2 This is the bottom hole structure of the product in Example 5. Detailed Implementation

[0035] The technical solutions in the embodiments of the present invention will now be clearly and completely described in conjunction with the accompanying drawings.

[0036] Example 1: A micro-conductive polyimide coated membrane with energy-releasing function, comprising a porous substrate and a composite coating coated on one side of the porous substrate. The composite coating comprises the following components: a polyimide matrix and modified carboxylated carbon nanotubes. The modified carboxylated carbon nanotubes are uniformly dispersed in the polyimide matrix, and the content of the modified carboxylated carbon nanotubes is 0.5 wt% of the polyimide matrix. The modified carboxylated carbon nanotubes are formed by modifying the surface of the carboxylated carbon nanotubes with a silane coupling agent. The polyimide matrix is ​​generated by in-situ polymerization of dianhydride monomers and diamine monomers. The dianhydride monomers contain DOPO derivative dianhydride monomers, and the DOPO derivative dianhydride monomers account for 3% of the total molar ratio of the dianhydride monomers. The porosity of the composite coating is 40%, the average pore size is 0.1-0.5 μm, and the pore size is gradient distributed along the thickness direction, with the surface pore size ≤0.2 μm and the bottom pore size ≥0.4 μm.

[0037] The porous substrate is a polyolefin-based membrane, which is either a polyethylene-based membrane or a polypropylene-based membrane, with a thickness of 3μm and a porosity of 30%.

[0038] The DOPO derivative dianhydride monomer is DOPO-HQDA, with the chemical formula:

[0039]

[0040] The silane coupling agent is γ-aminopropyltriethoxysilane, and the amount of γ-aminopropyltriethoxysilane added is 5% of the mass of the carboxylated carbon nanotubes.

[0041] Except for the DOPO derivative dianhydride monomer, the rest of the dianhydride monomers are biphenyltetracarboxylic dianhydride (BPDA); the diamine monomer is diaminodiphenyl ether (ODA).

[0042] Example 2: A micro-conductive polyimide coated membrane with energy-releasing function, comprising a porous substrate and a composite coating coated on both sides of the porous substrate. The composite coating comprises the following components: a polyimide matrix and modified carboxylated carbon nanotubes. The modified carboxylated carbon nanotubes are uniformly dispersed in the polyimide matrix, and the content of the modified carboxylated carbon nanotubes is 1 wt% of the polyimide matrix. The modified carboxylated carbon nanotubes are formed by modifying the surface of the carboxylated carbon nanotubes with a silane coupling agent. The polyimide matrix is ​​generated by in-situ polymerization of dianhydride monomers and diamine monomers. The dianhydride monomers contain DOPO derivative dianhydride monomers, and the DOPO derivative dianhydride monomers account for 5% of the total molar ratio of dianhydride monomers. The porosity of the composite coating is 50%, the average pore size is 0.1-0.5 μm, and the pore size is gradient distributed along the thickness direction, with the surface pore size ≤0.2 μm and the bottom pore size ≥0.4 μm.

[0043] The porous substrate is a polyolefin-based membrane, which is either a polyethylene-based membrane or a polypropylene-based membrane, with a thickness of 10 μm and a porosity of 40%.

[0044] The DOPO derivative dianhydride monomer is DOPO-HQDA, with the chemical formula:

[0045]

[0046] The silane coupling agent is γ-aminopropyltriethoxysilane, and the amount of γ-aminopropyltriethoxysilane added is 8% of the mass of the carboxylated carbon nanotubes.

[0047] Except for the DOPO derivative dianhydride monomer, the rest of the dianhydride monomers are pyromellitic dianhydride (PMDA); the diamine monomer is p-phenylenediamine (PDA); and the solvent is dimethylformamide (DMF).

[0048] Example 3: A micro-conductive polyimide coated membrane with energy-releasing function, comprising a porous substrate and a composite coating coated on one side of the porous substrate. The composite coating comprises the following components: a polyimide matrix and modified carboxylated carbon nanotubes. The modified carboxylated carbon nanotubes are uniformly dispersed in the polyimide matrix, and the content of the modified carboxylated carbon nanotubes is 1.5 wt% of the polyimide matrix. The modified carboxylated carbon nanotubes are formed by modifying the surface of the carboxylated carbon nanotubes with a silane coupling agent. The polyimide matrix is ​​generated by in-situ polymerization of dianhydride monomers and diamine monomers. The dianhydride monomers contain DOPO derivative dianhydride monomers, and the DOPO derivative dianhydride monomers account for 8% of the total molar ratio of the dianhydride monomers. The porosity of the composite coating is 60%, the average pore size is 0.1-0.5 μm, and the pore size is gradient distributed along the thickness direction, with the surface pore size ≤0.2 μm and the bottom pore size ≥0.4 μm.

[0049] The porous substrate is a polyolefin-based membrane, which is either a polyethylene-based membrane or a polypropylene-based membrane, with a thickness of 20 μm and a porosity of 50%.

[0050] The DOPO derivative dianhydride monomer is DOPO-HQDA, with the chemical formula:

[0051]

[0052] The silane coupling agent is γ-aminopropyltriethoxysilane, and the amount of γ-aminopropyltriethoxysilane added is 10% of the mass of carboxylated carbon nanotubes.

[0053] Except for the DOPO derivative dianhydride monomer, the remaining monomers are one or more of benzophenone tetracarboxylic dianhydride (BTDA), diphenyl ether tetracarboxylic dianhydride (ODPA), hexafluorodianhydride (6FDA), and bisphenol A type diether dianhydride (BPADA); the diamine monomer is one or more of 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFDB); and the solvent is dimethylacetamide (DMAc).

[0054] Example 4: Referring to Example 1, the dianhydride monomers, except for the DOPO derivative dianhydride monomers, are one or a mixture of two or more of biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), benzophenone tetracarboxylic dianhydride (BTDA), diphenyl ether tetracarboxylic dianhydride (ODPA), hexafluorodianhydride (6FDA), and bisphenol A type diether dianhydride (BPADA); the diamine monomers are one or a mixture of two or more of diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 4,4'-diaminodiphenylmethane (MDA), and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFDB); the solvent is one or a mixture of two or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAc).

[0055] Battery assembly and testing: The positive electrode (LiNi0.8Co0.1Mn0.1O2 (NCM811) active material, conductive agent, and binder) were mixed at a mass ratio of 96:2:2, coated onto aluminum foil, dried, and then rolled. The negative electrode (graphite active material, conductive agent, and binder) were mixed at a mass ratio of 95:2:3, coated onto copper foil, dried, and then rolled. The electrodes were stacked or wound in the order of "positive electrode-separator-negative electrode," and an electrolyte (1M LiPF6 in EC / DMC / EMC = 1:1:1) was injected, and the batteries were packaged into a pouch cell. Cycle performance was tested at a constant temperature of 25℃, with a charge / discharge voltage range of 2.8-4.3V and a constant current of 1C. After cycling, the batteries were disassembled to observe for lithium dendrite penetration into the separator and a flame retardant test was performed.

[0056] Example 5: A method for preparing a micro-conductive polyimide coated membrane with energy-releasing function, comprising the following steps:

[0057] A. Preparation of polyamic acid solution: Dissolve dianhydride monomer and diamine monomer in solvent according to the formulation of Example 1, add carboxylated carbon nanotubes and silane coupling agent, disperse for 2 hours to form a spinning solution with a solid content of 10 wt%.

[0058] B. Fiber preparation: The spinning solution was electrospinned to prepare nanofiber materials with a diameter of 100 nm;

[0059] C. High-temperature imidization: Under nitrogen protection, the nanofiber material is heat-treated at 250℃ for 1 hour to complete the polyimide ring-closure reaction and obtain high-temperature imide material;

[0060] D. Slurry preparation: The high-temperature imide material, water-based binder, and pore-forming agent are uniformly dispersed in water to prepare a slurry with a solid content of 3%.

[0061] E. Coating and Pre-curing: The slurry is uniformly coated on the surface of the porous substrate and pre-cured at 50°C for 5 minutes to obtain a pre-cured film;

[0062] F. Gradient drying: The pre-cured film is dried in two stages: the first stage is 60°C for 10 min, and the second stage is 120°C for 30 min to obtain a finished product with gradient pore size.

[0063] The water-based adhesive is a water-based PVDF emulsion.

[0064] In step A, the carboxyl group content of the carboxylated carbon nanotubes is 3 mmol / g, and in step D, the slurry viscosity is 500 mPa·s at 25°C.

[0065] The coating method in step E is spraying.

[0066] The pore-forming agent in step D is a mixture of polyethylene glycol and acetone in a mass ratio of 1:3.

[0067] Performance testing:

[0068] Flame retardancy: LOI = 36%, UL94 V0 rating;

[0069] Electrical conductivity: Surface resistivity = 1.8 Ω·cm 2 ;

[0070] Tensile strength: 322 MPa;

[0071] Cycle performance: NCM811 battery retains 82% capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 13°;

[0072] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 1200 hours of cycling.

[0073] Example 6: A method for preparing a micro-conductive polyimide coated separator with energy-releasing function, comprising the following steps:

[0074] A. Preparation of polyamic acid solution: Dissolve dianhydride monomer and diamine monomer in solvent according to the formulation of Example 2, add carboxylated carbon nanotubes and silane coupling agent, disperse for 2-4 hours to form a spinning solution with a solid content of 10-25 wt%.

[0075] B. Fiber preparation: The spinning solution is electrospinned to prepare nanofiber materials with a diameter of 100-800 nm;

[0076] C. High-temperature imidization: Under nitrogen protection, the nanofiber material is heat-treated at 250-400℃ for 1-4 hours to complete the polyimide ring-closure reaction and obtain high-temperature imide material;

[0077] D. Slurry preparation: The high-temperature imide material, water-based binder, and pore-forming agent are uniformly dispersed in water to prepare a slurry with a solid content of 3-20%.

[0078] E. Coating and Pre-curing: The slurry is uniformly coated on the surface of the porous substrate and pre-cured at 50-60℃ for 5-10 minutes to obtain a pre-cured film;

[0079] F. Gradient drying: The pre-cured film is dried in two stages: the first stage is 60°C for 10 min, and the second stage is 120°C for 30 min to obtain a finished product with gradient pore size.

[0080] The water-based adhesive is polyethylene oxide.

[0081] In step A, the carboxyl group content of the carboxylated carbon nanotubes is 4 mmol / g, and in step D, the slurry viscosity is 650 mPa·s at 25°C.

[0082] The coating method in step E is gravure coating.

[0083] The pore-forming agent in step D is a mixture of polyethylene glycol and acetone in a mass ratio of 1:4; the gradient pore size in step F is ≤0.2μm for the surface layer and ≥0.4μm for the bottom layer.

[0084] Performance testing:

[0085] Flame retardancy: LOI = 34%, UL94 V0 rating;

[0086] Electrical conductivity: Surface resistivity = 1.5 Ω·cm 2 ;

[0087] Tensile strength: 320 MPa;

[0088] Cycle performance: NCM811 battery retains 79% capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 15°;

[0089] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 1200 hours of cycling.

[0090] Example 7: A method for preparing a micro-conductive polyimide coated membrane with energy-releasing function, comprising the following steps:

[0091] A. Preparation of polyamic acid solution: Dissolve dianhydride monomer and diamine monomer in solvent according to the formulation of Example 3, add carboxylated carbon nanotubes and silane coupling agent, disperse for 4 hours to form a spinning solution with a solid content of 25 wt%.

[0092] B. Fiber preparation: The spinning solution was electrospinned to prepare nanofiber materials with a diameter of 800 nm;

[0093] C. High-temperature imidization: Under nitrogen protection, the nanofiber material is heat-treated at 400℃ for 4 hours to complete the polyimide ring-closure reaction and obtain high-temperature imide material;

[0094] D. Slurry preparation: The high-temperature imide material, water-based binder, and pore-forming agent are uniformly dispersed in water to prepare a slurry with a solid content of 20%.

[0095] E. Coating and Pre-curing: The slurry is uniformly coated on the surface of the porous substrate and pre-cured at 60°C for 10 minutes to obtain a pre-cured film;

[0096] F. Gradient drying: The pre-cured film is dried in two stages: the first stage is 60°C for 10 min, and the second stage is 120°C for 30 min to obtain a finished product with gradient pore size.

[0097] The water-based adhesive is polyethylene oxide.

[0098] In step A, the carboxyl group content of the carboxylated carbon nanotubes is 5 mmol / g, and in step D, the slurry viscosity is 800 mPa·s at 25°C.

[0099] The coating method in step E is the scraping method.

[0100] The pore-forming agent in step D is a mixture of polyethylene glycol and acetone at a mass ratio of 1:5; the gradient pore size in step F is ≤0.2μm for the surface layer and ≥0.4μm for the bottom layer.

[0101] Performance testing:

[0102] Flame retardancy: LOI = 38%, UL94 V0 rating;

[0103] Electrical conductivity: Surface resistivity = 2.2 Ω·cm 2 ;

[0104] Tensile strength: 325 MPa;

[0105] Cycle performance: NCM811 battery retains 80% of its capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 10°;

[0106] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 1200 hours of cycling.

[0107] Example 8: The water-based adhesive is one or more of the following: water-based PVDF emulsion, polyvinyl alcohol, polyethylene oxide, water-soluble acrylic adhesive, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyvinylpyrrolidone. The coating method in step E is one of the following: spray coating, blade coating, gravure coating, or dip coating. Comparative Example 1: Pure PE base film (without any coating).

[0108] Preparation method: A 7μm PE base film (40% porosity) was used directly without any coating treatment. Performance testing:

[0109] Flame retardancy: LOI = 18%;

[0110] Electrical conductivity: Surface resistivity = 5.2 Ω·cm 2 ;

[0111] Tensile strength: 320 MPa;

[0112] Cycle performance: NCM811 battery retains 38% capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 40°;

[0113] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 150 hours of cycling.

[0114] Failure Analysis: High-temperature melting caused a short circuit; there was no dendrite blocking ability; and the electrode pulverized severely after cycling. Comparative Example 2: Referring to Example 5, the coating was designed as a single coating, with only DOPO-HQDA added and no MWCNTS-COOH added.

[0115] Performance testing:

[0116] Flame retardancy: LOI = 35%;

[0117] Electrical conductivity: Surface resistivity = 8.5 Ω·cm 2 ;

[0118] Tensile strength: 323 MPa;

[0119] Cycle performance: NCM811 battery retains 65% capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 21°;

[0120] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 400 hours of cycling.

[0121] Failure analysis: The insulating properties of the flame retardant cause blockage of ion transport channels, and the high resistance leads to polarization during charging and discharging, resulting in accelerated capacity decay.

[0122] Comparative Example 3: Referring to Example 5, in step F, the drying was carried out directly at 120°C for 40 minutes.

[0123] Performance testing:

[0124] Flame retardancy: LOI = 33%;

[0125] Electrical conductivity: Surface resistivity = 4.2 Ω·cm 2 ;

[0126] Tensile strength: 255 MPa;

[0127] Cycle performance: NCM811 battery retains 63% capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 45°;

[0128] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 280 hours of cycling.

[0129] Failure analysis: High-temperature rapid drying leads to stress concentration in the coating, making it prone to cracking. Furthermore, at 120°C, acetone evaporates instantly, forming hard closed pores on the surface. The insufficient decomposition of PEG in the underlying layer results in insufficient pores, leading to uncontrolled pore size distribution and a decrease in porosity to 28%.

[0130] Comparative Example 4: Referring to Example 5, the flame-retardant component DOPO derivative dianhydride monomer in the dianhydride monomer was replaced with 6 wt% DOPO powder. Performance testing:

[0131] Flame retardancy: LOI = 29%;

[0132] Electrical conductivity: Surface resistivity = 4.5 Ω·cm 2 ;

[0133] Tensile strength: 310 MPa;

[0134] Cycle performance: NCM811 battery retains 61% capacity after 500 1C charge-discharge cycles; Electrolyte wettability: Contact angle = 40°;

[0135] Dendrite suppression effect: No short circuit was observed in the lithium symmetric battery after 320 hours of cycling.

[0136] Failure analysis: The addition method of flame retardant changed from polymerization to physical blending, resulting in uneven distribution of flame retardant and weak bonding with polyimide matrix. After cycling, DOPO migrates into the electrolyte, catalyzing electrolyte decomposition and accelerating the overall degradation of battery performance.

[0137] As can be seen from the above comparative examples and embodiments, without the PI coating, the PE base film melts and fails at high temperatures, proving that the coating is the core guarantee of thermal stability. A single flame-retardant coating leads to a surge in sheet resistivity (+372%) and a 21% decrease in cycle life, verifying that the MWCNTS-COOH conductive network is indispensable. In this patent, the flame-retardant-micro-conductive synergy (DOPO+MWCNTS-COOH), the structural gradient design (pore size stratification), and the in-situ polymerization process (avoiding phase separation) are all indispensable; the absence of any one of these elements will lead to a precipitous drop in performance.

[0138] The described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A micro-conductive polyimide coated membrane with energy-releasing function, comprising a porous substrate and a composite coating coated on at least one side of the porous substrate, characterized in that, The composite coating comprises the following components: a polyimide matrix and modified carboxylated carbon nanotubes. The modified carboxylated carbon nanotubes are uniformly dispersed in the polyimide matrix, and the content of the modified carboxylated carbon nanotubes is 0.5~1.5 wt% of the polyimide matrix. The modified carboxylated carbon nanotubes are formed by modifying the surface of carboxylated carbon nanotubes with a silane coupling agent. The polyimide matrix is ​​generated by in-situ polymerization of dianhydride monomers and diamine monomers. The dianhydride monomers contain DOPO derivative dianhydride monomers, and the DOPO derivative dianhydride monomers account for 3~8% of the total molar ratio of dianhydride monomers. The composite coating has a porosity of 40~60%, an average pore size of 0.1~0.5 μm, and a gradient distribution of pore size along the thickness direction, with a surface pore size ≤0.2 μm and a bottom pore size ≥0.4 μm. The DOPO derivative dianhydride monomer is DOPO-HQDA, and its chemical formula is [insert chemical formula here]. .

2. The micro-conductive polyimide coated membrane with energy-releasing function according to claim 1, characterized in that, The porous substrate is a polyolefin-based membrane, which is a polyethylene-based membrane or a polypropylene-based membrane, with a thickness of 3~20μm and a porosity of 30~50%.

3. The micro-conductive polyimide coated membrane with energy-releasing function according to claim 1, characterized in that, The silane coupling agent is γ-aminopropyltriethoxysilane, and the amount of γ-aminopropyltriethoxysilane added is 5-10% of the mass of carboxylated carbon nanotubes.

4. A method for preparing a micro-conductive polyimide coated separator with energy-releasing function as described in any one of claims 1 to 3, characterized in that, Includes the following steps: A. Preparation of polyamic acid solution: Dissolve dianhydride monomer and diamine monomer in solvent, add carboxylated carbon nanotubes and silane coupling agent, disperse for 2-4 hours to form a spinning solution with a solid content of 10-25 wt%. B. Fiber preparation: The spinning solution is electrospinned to prepare nanofiber materials with a diameter of 100~800 nm; C. High-temperature imidization: Under nitrogen protection, the nanofiber material is heat-treated at 250~400℃ for 1~4h to complete the polyimide ring-closure reaction and obtain high-temperature imide material; D. Slurry preparation: The high-temperature imide material, water-based binder, and pore-forming agent are uniformly dispersed in water to prepare a slurry with a solid content of 3-20%. E. Coating and Pre-curing: The slurry is uniformly coated on the surface of the porous substrate and pre-cured at 50~60℃ for 5~10 min to obtain a pre-cured film; F. Gradient drying: The pre-cured film is dried in two stages: the first stage is 60°C for 10 min, and the second stage is 120°C for 30 min to obtain a finished product with gradient pore size.

5. The method for preparing the micro-conductive polyimide coated membrane with energy-releasing function according to claim 4, characterized in that, The dianhydride monomers, except for DOPO derivative dianhydride monomers, are one or a mixture of two or more of biphenyltetracarboxylic dianhydride (BPDA), pyromellitic dianhydride (PMDA), benzophenone tetracarboxylic dianhydride (BTDA), diphenyl ether tetracarboxylic dianhydride (ODPA), hexafluorodianhydride (6FDA), and bisphenol A type diether dianhydride (BPADA); the diamine monomers are one or a mixture of two or more of diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 4,4'-diaminodiphenylmethane (MDA), and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFDB); the solvents are one or a mixture of two or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAc).

6. The method for preparing the micro-conductive polyimide coated separator with energy-releasing function according to claim 4, characterized in that, The water-based adhesive is one or more of the following: water-based PVDF emulsion, polyvinyl alcohol, polyethylene oxide, water-soluble acrylic adhesive, styrene-butadiene rubber, sodium carboxymethyl cellulose, and polyvinylpyrrolidone.

7. The method for preparing the micro-conductive polyimide coated separator with energy-releasing function according to claim 4, characterized in that, The carboxyl group content of the carboxylated carbon nanotubes in step A is 3~5 mmol / g, and the viscosity of the slurry in step D is 500~800 mPa·s at 25℃.

8. The method for preparing the micro-conductive polyimide coated membrane with energy-releasing function according to claim 4, characterized in that, The coating method in step E is one of spraying, scraping, gravure coating, or dip coating.

9. The method for preparing the micro-conductive polyimide coated membrane with energy-releasing function according to claim 4, characterized in that, The pore-forming agent in step D is a mixture of polyethylene glycol and acetone at a mass ratio of 1:3~5; the gradient pore size in step F is ≤0.2μm for the surface layer and ≥0.4μm for the bottom layer.

Citation Information

Patent Citations

  • PI matrix resin and flame-retardant colorless transparent polyimide film prepared from same

    CN109575285A

  • Flame-retardant lithium battery diaphragm and preparation method thereof

    CN118367302A

  • High-flame-retardant soluble polyimide film and preparation method thereof

    CN106750426A

  • Composite spinning fibre lithium ion battery diaphragm and preparation method thereof

    CN107369800A